2016
DOI: 10.1007/s11883-016-0611-4
|View full text |Cite
|
Sign up to set email alerts
|

Bempedoic Acid (ETC-1002): an Investigational Inhibitor of ATP Citrate Lyase

Abstract: Bempedoic acid (ETC-1002), a novel therapeutic approach for low-density lipoprotein cholesterol (LDL-C) lowering, inhibits ATP citrate lyase (ACL), an enzyme involved in fatty acid and cholesterol synthesis. Although rodent studies suggested potential effects of ACL inhibition on both fatty acid and cholesterol synthesis, studies in humans show an effect only on cholesterol synthesis. In phase 2 studies, ETC-1002 reduced LDL-C as monotherapy, combined with ezetimibe, and added to statin therapy, with LDL-C low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 25 publications
0
53
0
6
Order By: Relevance
“…206 Importantly, several ACLY inhibitors including ETC-1002 (Phase 2/3 clinical trials) and hydroxycitrate (randomised control trials) have shown high efficacy in lowering low-density lipoprotein-cholesterol and good tolerability in patients with cardiovascular disease and type 2 diabetes (Table 1), thus indicating that ACLY inhibition could represent a well-tolerated therapeutic strategy. [207][208][209][210][211] There is considerable interest in ACLY as a target for anticancer drugs; however, clinical trial studies in this context are far more limited when compared with dyslipidaemia cases. Nevertheless, there is a plethora of preclinical evidence to support the integral role of ACLY in tumorigenesis and the potential clinical benefits for its selective inhibition.…”
Section: Therapeutically Exploiting Fatty Acid Metabolism In Cancermentioning
confidence: 99%
“…206 Importantly, several ACLY inhibitors including ETC-1002 (Phase 2/3 clinical trials) and hydroxycitrate (randomised control trials) have shown high efficacy in lowering low-density lipoprotein-cholesterol and good tolerability in patients with cardiovascular disease and type 2 diabetes (Table 1), thus indicating that ACLY inhibition could represent a well-tolerated therapeutic strategy. [207][208][209][210][211] There is considerable interest in ACLY as a target for anticancer drugs; however, clinical trial studies in this context are far more limited when compared with dyslipidaemia cases. Nevertheless, there is a plethora of preclinical evidence to support the integral role of ACLY in tumorigenesis and the potential clinical benefits for its selective inhibition.…”
Section: Therapeutically Exploiting Fatty Acid Metabolism In Cancermentioning
confidence: 99%
“…17 The study of healthy volunteers demonstrated a mean decrease in LDL-C levels of 36% in the bempedoic acid group compared to a 4% increase in the placebo group (40% placebo-adjusted LDL-C reduction; p <0.0001). 18 , 19 The phase I trials demonstrated that there were no adverse effects related to bempedoic acid dosing and bempedoic acid was overall determined to be safe to proceed with phase II trials.…”
Section: Phase I Trialsmentioning
confidence: 99%
“…LDL-C levels were lowered by 22% in the bempedoic acid arm and no reduction was seen in the placebo arm ( p <0.0001). 19 , 25 In a study by Ballantyne et al, 26 134 patients with LDL-C levels between 115 and 220 mg/dL while taking atorvastatin ≤20 mg daily, pravastatin ≤40 mg daily, rosuvastatin ≤10 mg daily, or simvastatin ≤20 mg daily were randomized to receive bempedoic acid 120 mg, 180 mg, or placebo daily for 12 weeks. Patients who had bempedoic acid added onto concurrent statin therapy experienced an LDL-C reduction of 17% (120 mg daily) and 24% (180 mg daily) compared to 4% with placebo ( p =0.0055 and p <0.0001, respectively).…”
Section: Phase II Trialsmentioning
confidence: 99%
“…The ACL inhibitor ETC-1002 (bempedoic acid) has been found to lower cholesterol biosynthesis by depriving cells of the necessary substrates. To date, studies either as monotherapy or as combination therapy with statins have shown positive results, without significant side effects (Bilen and Ballantyne, 2016 ; Lammel Lindemann and Webb, 2016 ). The promising LDL-lowering effects of ETC-1002 from phase II trials remain to be confirmed by a phase III programme assessing its efficacy, safety and long-term outcomes (Bilen and Ballantyne, 2016 ).…”
Section: Management Of Fhmentioning
confidence: 99%
“…To date, studies either as monotherapy or as combination therapy with statins have shown positive results, without significant side effects (Bilen and Ballantyne, 2016 ; Lammel Lindemann and Webb, 2016 ). The promising LDL-lowering effects of ETC-1002 from phase II trials remain to be confirmed by a phase III programme assessing its efficacy, safety and long-term outcomes (Bilen and Ballantyne, 2016 ). Since this agent has been also found to reduce C-reactive protein levels, better CVD outcomes may be possible through its implication in pro-inflammation processes (Penson et al, 2017 ).…”
Section: Management Of Fhmentioning
confidence: 99%